Strategi Penanggulangan Banjir Oleh Dinas Pekerjaan Umum Dan Penataan Ruang (PUPR) Di Kota Pekanbaru: Dalam Tinjauan Analisis SWOT - Sonia, Novi; Ummul Fithriyyah, Mustiqowati (LPPM STIA Lancang Kuning Dumai, 2023)
This study aims to analyze the flood prevention strategy by the Public Works and Spatial Planning (PUPR) Office in Pekanbaru City. The type of research used is descriptive qualitative with analytical techniques. The theory used to achieve the desired target is Rangkuti's theory of SWOT analysis which is to determine strengths, weaknesses, opportunities and threats in looking at internal and external factors in flood control and then create a SWOT matrix based on the results of internal environmental analysis (IFAS) and external environmental analysis (EFAS) so that it can determine the best strategy in the flood management process in Pekanbaru city. From the results of the internal environment analysis (IFAS), the strengths of the strategic factors obtained a total score of -0.62 and their weaknesses with a total score of -0.3. And the results of the analysis of the external environment (EFAS) the opportunity factor obtained a score of -1.14 and a threat with a total score of -0.6. The analysis on the SWOT diagram illustrates that the flood management strategy by the public works and spatial planning department in Pekanbaru City is in the implementation of a weak but very good strategy. This was obtained based on the results of the SWOT analysis diagram coordinates where the X value (-0.3) and Y value (-0.6).